Moralizing meat consumption: Bringing food and feeling into education for sustainable development. Issue 7 (October 2019) - Bruckner, Heide K; Kowasch, Matthias
This article critiques the way the topic of meat and its consumption is addressed in geography education within the remit of education for sustainable development (ESD). We argue that current approaches perpetuate normative food discourse by: (a) framing participation in the food system solely in terms of consumption; (b) simplifying and moralizing food systems as 'good' or 'bad'; and (c) largely omitting animals from a discussion of meat and agriculture. As a result, students learn that their role is to consume 'good' not 'bad' meat, but are ill-equipped to analyse the political–economic, cultural and affective dimensions of food. Meat and consumption topics, although rarely addressed, fall under the broader pedagogy of ESD. Although emancipatory approaches to ESD explore contradictions inherent in and personal aspects of sustainability, ESD in practice often leads to binary schemata of 'right' and 'wrong'. Based on our qualitative review of geography curricula in Austria and Germany (Lower Saxony and Bremen), we find that they neglect meat production and consumption, but that these subjects can be addressed within broader topics about sustainability and agricultural land use. Interviews with secondary school teachers and students indicate that ESD ignores the interpersonal, relational and more-than-human elements of food systems. However, we show that students still rank animal welfare as an important component of sustainability. This indicates that they are influenced by education beyond institutional settings and, furthermore, highlights opportunities for making students aware of the visceral (dis)connections they make between taste and political economy. Finally, we suggest future directions for ESD in order that these links can be explored, probing students to develop their own ethics of the gut.